E-SCIENCE IN THE ARTS AND HUMANITIES. - ROBEY, DAVID (International Journal of Humanities & Arts Computing: A Journal of Digital Humanities, 2007)
The article focuses on the impact of e-Science on the arts and humanities (A&H) field. It mentions the necessity of using e-Science technologies for the extension and development of the A&H community, and reports the e-Science funding given to several councils in Great Britain. It discusses the A&H e-Science development project of the British Arts and Humanities Research Council (AHRC). E-Science and its data grid technology have several applications for A&H which include digitization and cataloging of a variety of data. It also discusses the e-Science projects, demonstrations, and workshops organized for the A&H community in Great Britain. Also discussed is the Access Grid technology developed for A&H researchers.